2021
DOI: 10.1002/ana.26073
|View full text |Cite
|
Sign up to set email alerts
|

Foslevodopa/Foscarbidopa: A New Subcutaneous Treatment for Parkinson's Disease

Abstract: The aim was to demonstrate that continuous s.c. infusion of a soluble levodopa (LD)/carbidopa (CD) phosphate prodrug combination effectively delivers stable LD exposure via a minimally invasive and convenient mode and has the potential to treat Parkinson's disease (PD) patients who are not well controlled on oral medication. Methods: Foslevodopa and foscarbidopa were prepared and the equilibrium solubility and chemical stability examined in aqueous media with different values of pH. Solutions of foslevodopa/fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
1
43
0
1
Order By: Relevance
“…Previous work demonstrated that foslevodopa/ foscarbidopa SC infusion was able to maintain stable LD exposure in healthy volunteers [4]; however, tolerable LD exposures in healthy volunteers are notably lower than what is reported in PD patients. High LD exposures in non-dopamine deficient healthy volunteers are associated with troublesome side effects making the exploration of higher foslevodopa/foscarbidopa doses in the healthy volunteer study population impractical.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous work demonstrated that foslevodopa/ foscarbidopa SC infusion was able to maintain stable LD exposure in healthy volunteers [4]; however, tolerable LD exposures in healthy volunteers are notably lower than what is reported in PD patients. High LD exposures in non-dopamine deficient healthy volunteers are associated with troublesome side effects making the exploration of higher foslevodopa/foscarbidopa doses in the healthy volunteer study population impractical.…”
Section: Discussionmentioning
confidence: 85%
“…Foslevodopa/foscarbidopa is in development for the treatment of motor complications for patients with advanced PD (aPD) and is intended to be delivered continuously for 24 h/day. The stability of LD exposure from foslevodopa/foscarbidopa CSCI has been already demonstrated in healthy volunteers [4]. The current work characterizes the LD and CD pharmacokinetics (PK) following SC infusions of foslevodopa/foscarbidopa delivered at four different infusion rates in PD patients.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…These include continuous intestinal delivery of levodopa-carbidopa gel via percutaneous gastrojejunostomy [92], which, according to some studies, is comparable to DBS for the treatment of motor fluctuations in advanced PD [93]. Others include inhaled levodopa-carbidopa [94] and a subcutaneous levodopa-carbidopa infusion [95].…”
Section: New Routes Of L-dopa Deliverymentioning
confidence: 99%